Deteksi Penyakit Alopecia Areata Menerapkan Metode Laplacian of Gaussian - Safitri, Nur Irma (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Alopecia areata is hair loss caused by an attack by the body's own immune system and occurs on the scalp, and can also occur in other parts of the body where hair is grown. This baldness can be suffered by anyone, both men and women, a disease whose job is to protect the body from viruses and bacteria. Symptoms are mainly rounded pattern baldness and baldness can also extend to the entire scalp. Alopecia areata an unpredictable condition, bald patches can grow back (heal spontaneously) in a few months or years without treatment but do therapy such as giving corticosteroid injections, which is a line therapy for 4-6 weeks of hair growth but patients who have extensive baldness tend to have poor response. In addition to giving injections, corticosteroid cream can also be done by applying the cream 2 times per day. In a hair, the process of checking the shape of the hair that is not falling and that is falling will be carried out. Each image will have a different result. In this case, the image will create a process for detecting hair loss disease with the Laplacian of gaussian method which results in a difference from each image so that it makes classification of each image easier.